PENEGAKAN HUKUM TERHADAP PERSOLAN KORUPSI DI INDONESIA, PENDEKATAN SISTEM HUKUM L.W FRIEDMAN - Firmansyah (FAKULTAS HUKUM UM PAREPARE, 2022)
This study aims to determine the factors causing corruption and law enforcement efforts on the issue of corruption. This study uses a normative approach, data analysis is carried out using descriptive-qualitative analysis. The findings obtained from this study include that the factors causing corruption are internal factors and internal factors and one of the law enforcement efforts that can be done is using the L.W Friedaman approach by improving and combining 3 (three) elements, namely substance/regulation, structure/institutional and culture/attitudes or values. In addition to the penal approach, another thing that can also be done is the non-penal approach